A Goldstein's Type Projection Method for a Class of Variant Variational Inequalities (Journal of Computational Mathematics, 1999)
Some optimization problems in mathematical programming can be translated to a variant variational inequality of the following form: Find a vector $\u^*$,such that $$Q(u^*)∈Ω,(v-Q(u^*))^Tu^* ≥ 0, ∀_v∈Ω.$$. This paper presents a simple iterative method for solving this class of variational inequalities. The method can be viewed as an extension of the Goldstein's projection method. Some results of preliminary numerical experiments are given to indicate its applications.
Keywords: Variational inequality; Goldstein Projection method.